THE EFFECT OF FOREIGN EXCHANGE RESERVES, EXCHANGE RATES AND LIBOR INTEREST RATE ON FOREIGN DEBT - Kasmianti Kasmianti; Fitriyani Fitriyani; Miksalmina Miksalmina (Syiah Kuala University, 2022)
Foreign debt is one of the alternative incomes or sources of domestic capital financing to cover the lack of development capital. The purpose of this research is to assess the short-term and long-term impact of foreign exchange reserves, the rupiah exchange rate, and foreign interest rate on Indonesia's foreign debt from 2008 to 2020. The results of VECM model show that foreign exchange reserves have a positive and significant effect on foreign debt in the short term, but a negative and significant effect on foreign debt in the long run. The rupiah exchange rate has no influence on foreign debt in the near term, but it has a negative and considerable effect in the long term. Then, in the short and long run, foreign interest rate has no influence on Indonesia's foreign debt. Hence, the government is expected to take appropriate policy steps to lessen its reliance on foreign debt. One of them is to optimize the use of foreign debt for productive purposes, so increasing foreign exchange reserves while decreasing the amount of debt borrowed.